Human responses to climate change: social representation, identity and socio-psychological action - Jaspal, Rusi; Nerlich, Brigitte; Cinirella, Marco (Taylor & Francis, 2014)
Climate change is one of the most important global challenges in the twenty-first century, given that a changing climate is likely to have negative and potentially irreversible consequences for the environment and human beings. Drawing upon Social Representations Theory (SRT) and Identity Process Theory (IPT) from social psychology, we argue that research should focus upon, and successfully integrate, three levels of analysis, namely (1) how climate change knowledge is constructed and circulates (social representation); (2) the role of identity in relation to these representations (identity); and (3) how people might respond to them (action). It is suggested that identity processes may determine how people process social representations of climate change, and that they mediate the link between representations and environmental behavior. Understanding human responses to climate change necessitates an integrative social sciences perspective, in terms of disciplinary, theoretical, and methodological approaches.